2015
DOI: 10.1371/journal.pone.0141123
|View full text |Cite
|
Sign up to set email alerts
|

Radical Prostatectomy versus External Beam Radiotherapy for cT1-4N0M0 Prostate Cancer: Comparison of Patient Outcomes Including Mortality

Abstract: BackgroundAlthough radical prostatectomy (RP) and external beam radiotherapy (EBRT) have been considered as comparable treatments for localized prostate cancer (PC), it is controversial which treatment is better. The present study aimed to compare outcomes, including mortality, of RP and EBRT for localized PC.MethodsWe retrospectively analyzed 891 patients with cT1-4N0M0 PC who underwent either RP (n = 569) or EBRT (n = 322) with curative intent at our single institution between 2005 and 2012. Of the EBRT pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The success in BRFS with high-dose in RT was not achieved in terms of OS. In agreement with other studies 14 , 16 , 17 , 20 - 22 , mean age at diagnosis in patients receiving RT in our study was significantly higher than that in patients receiving RP. Patients receiving RP were generally in the low and intermediate risk groups, and those undergoing RT were more populated in the high risk group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The success in BRFS with high-dose in RT was not achieved in terms of OS. In agreement with other studies 14 , 16 , 17 , 20 - 22 , mean age at diagnosis in patients receiving RT in our study was significantly higher than that in patients receiving RP. Patients receiving RP were generally in the low and intermediate risk groups, and those undergoing RT were more populated in the high risk group.…”
Section: Discussionsupporting
confidence: 93%
“…The low risk group had the highest age at diagnosis in the RT arm in our study, and also the highest mortality rates Analysis of causes of death revealed that patients in the low risk group died from chronic diseases and other causes. Similar studies have also frequently reported deaths unrelated to prostate cancer among causes of death in the RT arm 16 , 17 , 23 , 24 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…How patients with GP5 or those with a high probability of having GP5 can be treated? We have previously investigated the clinical significance of salvage RT and salvage ADT for locally advanced PC (19)(20)(21). Men in the high-risk group that received RP following radiotherapy had significantly better cancer-specific and overall survival outcomes than patients who had firstly received radiotherapy (19).…”
Section: Discussionmentioning
confidence: 99%
“…The OR of 2-year and 5-year BDFS also showed a better result among patients received EBRT, which was consistent with subgroup analyses of risk stratification. The different nadir levels were used in defining the biochemical failure, the post-radiotherapy patients were regarded as biochemical failure with higher PSA level, thus the result of BDFS might not reflect the mortality [ 20 ]. And the higher rate of biochemical failure for postoperative patients might contribute to the higher use of salvage therapies.…”
Section: Discussionmentioning
confidence: 99%